PENGEMBANGAN SELF HELP BOOK UNTUK PEMAHAMAN SISWA TENTANG PROKRASTINASI AKADEMIK - Nurfadilah Dilah; Rochani; Raudah Zaimah Dalimunthe (Jurnal Genta Mulia, 2024)
One effort to provide students with an understanding of academic procrastination is by developing innovative, effective and efficient information media. This research aims to develop an information media, namely an e-book with the title "Self Help Book Academic Procrastination" which is feasible and can provide students with an understanding of academic procrastination. This e-book is designed to be an information medium and can be studied, especially for students who have learning problems, as well as facilitating guidance and counseling teachers in providing guidance and counseling services to students. The method used in this research is the research and development (R&D) method with the ADDIE model which has 5 stages, namely (analysis, design, development, implementation and evaluation). The data collection technique used was product validation testing with material media experts, language experts and also practitioner experts. The statistical data analysis technique used in product feasibility testing is simple random sampling which is used for research sampling. The results of the product feasibility test carried out by experts reached an average of 85%, including it in the category of fit for use and can be implemented by students.